2017
DOI: 10.1038/cr.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

5-methylcytosine promotes mRNA export — NSUN2 as the methyltransferase and ALYREF as an m5C reader

Abstract: 5-methylcytosine (m5C) is a post-transcriptional RNA modification identified in both stable and highly abundant tRNAs and rRNAs, and in mRNAs. However, its regulatory role in mRNA metabolism is still largely unknown. Here, we reveal that m5C modification is enriched in CG-rich regions and in regions immediately downstream of translation initiation sites and has conserved, tissue-specific and dynamic features across mammalian transcriptomes. Moreover, m5C formation in mRNAs is mainly catalyzed by the RNA methylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

62
988
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(1,125 citation statements)
references
References 72 publications
(109 reference statements)
62
988
2
3
Order By: Relevance
“…The extensive study by Yang et al in May issue of Cell Research significantly upgrades the standing of m 5 C in the epitranscriptome field [7]. The detailed unique m 5 C topology, as explored in this study, differs from that reported before.…”
contrasting
confidence: 51%
“…The extensive study by Yang et al in May issue of Cell Research significantly upgrades the standing of m 5 C in the epitranscriptome field [7]. The detailed unique m 5 C topology, as explored in this study, differs from that reported before.…”
contrasting
confidence: 51%
“…First, we compared the amino acid sequences of the four Arabidopsis ALY proteins (ALY1- modification of mRNAs and other RNAs in Arabidopsis (David et al 2017) and that 175 mammalian ALY preferentially binds to m 5 C-modified RNA (Yang et al 2017). Therefore,…”
Section: Aly Proteins In Arabidopsis and Other Plants 127mentioning
confidence: 99%
“…Like mammalian ALY (Yang et al 2017), Arabidopsis ALY1 396 exhibits a significantly higher affinity for m 5 C-modified RNA. The m 5 C modification is mammals (Yang et al 2017), a mechanism that may be conserved in plants (David et al 399 2017). whereas the other ALY proteins were also expressed in the surrounding sporophytic tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6, 7] Additionally, it is proposed that m 5 C is essential for mRNA export and post-transcriptional regulation. [8] Significant enrichment of hm 5 C in polyadenylated RNA compared to total RNA further suggests that biosynthesis of hm 5 C might be a part of a dynamic regulatory mechanism of RNA. [6b, 9] The f 5 C modification is prevalent at the wobble position of an anticodon loop of mitochondrial methionine tRNA in many species, including humans.…”
mentioning
confidence: 99%